2002
DOI: 10.1002/ptr.1018
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different crude extracts of Ocimum sanctum on noise stress

Abstract: Our previous studies have shown that the ethanolic extract of Ocimum sanctum (OS) leaves was effective in alleviating the noise stress induced changes. Hence in this study, we have investigated the effectiveness of different types of crude OS extracts on some of the stress parameters after noise stress. The results of this study has shown that the active principle responsible for antistressor effect of ethanolic extract is also present in cold homogenised leaf extract of OS also. Hot extracts slightly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Similarly, experimental studies have shown that tulsi helps reduce the effects of acute and chronic noise-induced stress in experimental animals, with enhancement of neurotransmitter and oxidative stress levels in discrete brain regions along with improved immune, ECG and corticosteroid responses. [ 42 43 44 45 ]…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, experimental studies have shown that tulsi helps reduce the effects of acute and chronic noise-induced stress in experimental animals, with enhancement of neurotransmitter and oxidative stress levels in discrete brain regions along with improved immune, ECG and corticosteroid responses. [ 42 43 44 45 ]…”
Section: Introductionmentioning
confidence: 99%
“…It reacts within split seconds to help the body adjust to this stressful situation by releasing hormones [2]. Researchers demonstrated that noise exposure is a potent stressor that increases the levels of the stress hormone, corticosterone [6]. Noise stress effects are not sudden and catastrophic but gradual and insidious [2].…”
Section: Introductionmentioning
confidence: 99%
“…Only the freshly prepared extract was used for the study. 8 Drugs: Following drugs and chemicals were used: indomethacin (Indocap, Jagsonpal Pharmaceuticals, India), phenytoin (M-Toin, Medopharm, India), sodium valporate (Encorate, Sun Pharmaceuticals, India), diazepam (Valium, Piramal Healthcare, India), pentylenetetrazole (Sigma Chemicals, USA), pentobarbitone sodium (LobaChemie, India), morphine (Martindale Pharmaceuticals, UK) and acetic acid (Qualigens fine chemical, India).…”
Section: Extract Preparation: Og Was Collected From Thickmentioning
confidence: 99%
“…The dose of the test drug was chosen according to the study done Archana et al and Volume Guidelines for Compound Administration. 8,9 All standard drugs were administered to the animals through oral route 45 minutes before the experiments. The experiment was conducted on 7th day, 45 minutes after the last test drug administration.…”
Section: Experimental Designmentioning
confidence: 99%